Вечный зов: роман : в 2 кн. (А. С. Иванов) - Иванов Анатолий Степанович (1993)
Экземпляры: аб (20210302) / Инвентарный номер: 56463 / Цена: 40.00 / Сис.шифр: Р2 / Авт.знак: И 20 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6